Community Service Awareness of Environmental Law with A Pollution Control and Environmental Management Program in the Village of Kading - Sandra, Gustika; Suriyati, Suriyati; Rasyid, Mukhawas (Journal of Universal Community Empowerment Provision, 2023)
Government as underwriter answer to well-being its people own not quite enough answer big in effort think and realize formation preservation environment live. As good citizens, society must own high level of concern to sustainability environment live around it in accordance with Conditions Tree Management Environment Life based on Law no. 4 of 1982. Management environment government has declared for applied in the community environment with cope case pollution. supervise material dangerous and poisonous, do evaluation analysis about impact environment as well as various management and protection movements law environment. Activity Devotion This carried out in the village Kading Bone Regency which was carried out by Andi Sudirman University lecturers together with student. Activity This carried out in 3 stages that is Focus Group Discussion (FGD), socialization policy law environment and agreements in commitment together to use Control Pollution Environment. Opportunities for students to enrich themselves through activities and ideas outside of learning activities and provide scholarship opportunities for smart students by using their creativity and encouraging special education in 3T places so that they are the same as schools that have quality education according to national standards.